The Ability of Problem-Solving for Eighth Grade Student on Cooperative Problem Solving Learning Assisted by GeoGebra 3D - Nursasongko, Aditya; Mariani, Scolastika; Dwijanto, Dwijanto (Unnes Journal of Mathematics Education Research, 2020)
Mathematics learning is very important given in order to the students can have problem-solving abilities. This study aims to test the effectiveness of cooperative problem solving (CoPS) learning assisted by the GeoGebra 3D on students' problem-solving abilities and describe problem solving abilities in terms of students' GeoGebra 3D usage. This research is a type of quantitative and qualitative. The study was conducted in a junior high school named SMP Islam Al Azhar 14 Semarang in the 2018/2019 academic year. The research subjects were eighth grade students consisting of one experimental class with cooperative problem solving learning assisted by GeoGebra 3D treatment and one control class. Then two students were selected for each of the high, medium, and low GeoGebra 3D usage categories. Hypothesis testing uses one-party proportion test and average difference test. The results of the study showed that cooperative problem solving (CoPS) learning assisted by GeoGebra 3D was effective on students' problem-solving abilities. Students with medium and high usage categories of GeoGebra 3D can reach all indicators of problem-solving even though several indicators of problem-solving are achieved with insignificant errors. Students with medium and high GeoGebra 3D usage categories can implement the steps of problem-solving according to Polya's steps, even they are as good at the carry out the plan step. Students with low GeoGebra 3D usage category cannot carry out the Polya's steps well. Students with low GeoGebra 3D usage category faced difficulties to devise problem-solving plan, carry out problem-solving plan, and looking-back step is not done.